Effect of Fiscal Decentralization and Institutional Performance on Inclusive Growth in Indonesia: Institut Pertanian Bogor (Jurnal Ekonomi dan Kebijakan Pembangunan, 2025)
Inclusive growth is an economic growth that prioritizes the increased economic growth, reduced unemployment, and reduced income inequality. The objectives of this research are: (1) to analyze the development of factors that influence inclusive growth; and (2) examine the influence of fiscal decentralization, democracy index performance, and other factors on inclusive growth. The research  method used in this study is  panel data based on Fixed Effect Model (FEM) and Klassen Typology. The data are 34 provinces in Indonesia, range from 2016 to 2020. Dependent variable used in this research is inclusive economic development index. On the other hand, independent variables used are fiscal decentralization, Indonesian democracy index (IDI), gender development index (GDI), mean years of schooling, gross fixed capital formation, and environmental performance index. The results of this study show that democracy index and mean years of schooling have affected significantly and positively on inclusive growth. Meanwhile, fiscal decentralization degree and environmental performance index have affected significantly and negatively on inclusive growth.